Recent Advances in Transition Metal-Catalyzed Methylation Reactions - Yan, Guobing; Borah, Arun Jyoti; Wang, Lianggui; Yang, Minghua (Advanced synthesis & catalysis, 2015)
Methylation is one of the most fundamental synthetic transformations in organic chemistry, but usually employs hazardous and toxic reagents, such as methyl iodide, dimethyl sulfate, diazomethane and dimethyl carbonate. In order to address sustainable development and green strategies, synthetic chemists have devoted much effort to the discovery and development of new methylating reagents, which are successfully being applied in transition metal‐catalyzed cross‐coupling reactions. In this review, recent advances in this area are summarized, mainly including C‐methylation, N‐methylation and O‐methylation. The respective reaction mechanisms are also discussed.